Study guide for use with fundamental accounting principles - Larson, Kermit D. (Chicago : Irwin, 1996)
Business
Keywords: Accounting; Financial statements; Merchandising; Accounting systems; Investment; Managerial accounting; Cost accounting; Capital budgeting